Boks : zawody o mistrzostwo I-szej ligi. (Gdańsk : [s.n.], 1954)
Afisz inf. o zawodach, które miały miejsce 28.11.1954 w Gdańsku-Wrzeszczu.
Keywords: Boks -- Polska -- 1945-1970.; Boks -- Polska -- Gdańsk -- 1945-1970 -- druki ulotne; Boks -- Polska -- Gdańsk -- 1945-1970 -- plakaty